Carbon dioxide reforming of methane over Ni/gamma-Al2O3, Ni/ZSM-5, Co/gamma-Al2O3 & Co/ZSM5 - Saidina Amin, Nor Aishah; Chin, Sean Hon Keong; Chang, Nee San; Chan, Huang Shean; Teo, Puay Tiang (Faculty of Chemical and Natural Resources Engineering, UTM, 2001)
The catalytic performance of carbon dioxide reforming of methane to synthesis gas (H2+CO) was studied over Ni/gamma-Al2O3, Ni/ZSM-5, Co/gamma-Al2O3 and Co/ZSM5. These catalysts were prepared using the incipient wetness impregnation method with 1 wt % of the metal. The catalysts were characterized using X-Ray Diffraction (XRD). The performance of the catalysts was tested in a lab-scale fixed-bed reactor with a reactant feed ratio of CH4:CO2 = 1:1, and F/W = 22,000 mL/g.hr. 1 g catalyst was loaded into the reactor for five hours of testing using 300 mL/min N2 as the diluent. The experimental result displayed that the methane and carbon dioxide conversion decreased in the order: Co/gamma-Al2O3> Ni/gamma-Al2O3>CO/ZSM-5>Ni/ZSM5, the CO production and selectivity decreased in the order: Ni/gamma-Al2O3>CO/ZSM5>Ni/ZSM5>Co/gamma-Al2O3 and catalyst stability decreased in the order:Co/ZSM5>Co/gamma-Al2O3>Ni/ZSM5> Ni/gamma-Al2O3. From the experimental result, Co/ZSM5 exhibited a good performance in catalyst activity and stability.